SOME RECOMMENDATIONS FOR TEACHING THE ENGLISH LANGUAGE IN ELEMENTARY SCHOOLS WITH LISTENING SKILL (Scientific journal of the Fergana State University, 2023)
The use of listening skillin teaching in the elementary grades of the school makes classes interesting and varied.This article discusses assignment for students learning a foreign language.